"دور إدارة المعرفة في تحسين الأداء في المؤسسات الاقتصادية دراسة حالة مؤسسة توزيع الكهرباء والغاز – سونلغاز - بالوادي" - عبد النور, كحلاوي; كريمة, تامة; مرجانة, حبى (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى التعرف على دور إدارة المعرفة في تحسين الأداء في المؤسسة الاقتصادية الجزائرية، وبغرض الإحاطة بالموضوع من جميع جوانبه تم الاعتماد على المنهج الوصفي التحليلي، من خـلال التعريـف بـإدارة المعرفة ومنهجيتها، وتقديم الإطار النظري للأداء في المؤسسة، وإبراز تأثير أبعاد إدارة المعرفة علـى الأداء في المؤسسة، ومن خلال التحليل الإحصائي لبيانات عينة الدراسة، وقفنا على إثبات وجود دور ايجابي ومعنوي لإدارة المعرفة في تحسين أداء بمؤسسة الكهرباء والغاز – سونلغاز- بالوادي. This study aims to identify the role of knowledge management in improving performance in the Algerian economic institution, and in order to understand the subject in all its aspects, the descriptive analytical approach was relied upon, by defining knowledge management and its methodology, presenting the theoretical framework for performance in the institution, and highlighting the impact of the dimensions of knowledge management on Performance in the enterprise, and through statistical analysis of the data of the study sample, we have proven that there is a positive and significant role for knowledge management in improving the performance of the Electricity and Gas Corporation - Sonelgaz - in El Oued
Keywords: المعرفة- إدارة المعرفة– الأداء.; Knowledge - knowledge management - performance